2017
DOI: 10.1016/j.ajpath.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-to-Mesenchymal Transition in Bone Marrow and Spleen of Primary Myelofibrosis

Abstract: Primary myelofibrosis is characterized by the development of fibrosis in the bone marrow that contributes to ineffective hematopoiesis. Bone marrow fibrosis is the result of a complex and not yet fully understood interaction among megakaryocytes, myeloid cells, fibroblasts, and endothelial cells. Here, we report that >30% of the endothelial cells in the small vessels of the bone marrow and spleen of patients with primary myelofibrosis have a mesenchymal phenotype, which is suggestive of the process known as en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“… 96 Further, Erba et al showed that release and activation of TGF-β1 by Mks and platelets, forced endothelial cells from the BM microvasculature of PMF patients, and mouse model of PMF, to acquire a mesenchymal phenotype through Endothelial Mesenchymal Transition (EndMT), during the development of fibrosis. 97 …”
Section: Megakaryocyte-derived Pro-fibrotic Cytokines In Bone Marrow mentioning
confidence: 99%
“… 96 Further, Erba et al showed that release and activation of TGF-β1 by Mks and platelets, forced endothelial cells from the BM microvasculature of PMF patients, and mouse model of PMF, to acquire a mesenchymal phenotype through Endothelial Mesenchymal Transition (EndMT), during the development of fibrosis. 97 …”
Section: Megakaryocyte-derived Pro-fibrotic Cytokines In Bone Marrow mentioning
confidence: 99%
“…Recently, Erba et al . reported that endothelial‐to‐mesenchymal transition (EndoMT) produces αSMA expression of splenic sinus endothelial cells (SECs) and fibrosis in the spleen of patients with primary myelofibrosis . Endothelial cells contribute to neovascularization of the injury region and promote repair .…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial‐to‐mesenchymal transition is a relatively common reaction of different types of endothelial cells. As its name implies, during EndoMT, endothelial cells show gene expression patterns similar to those of myofibroblasts, including gene expression of αSMA, fibroblast‐specific protein‐1, and collagen type I . Portal hypertension causes endothelial dysfunction in the splanchnic and systemic circulation .…”
Section: Discussionmentioning
confidence: 99%
“…In reality, JAK2-V617F has been proved in connection with Myeloproliferative Neoplasams (MPNs) [9][10]. As we all know, MPNs are a group of hematopoietic stem cell disorders characterized by clonal proliferation of myeloid-lineage cells [11].…”
Section: Discussionmentioning
confidence: 99%